El Excentrico, 1960-08-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
August 5, 1960 [5 de Agosto de 1960]. Ano 10, No 22. Cover has a photgraph of C.S.O Beauty Contest winner Vickie Guitierrez with runner-ups, Nancy Ortiz and Dolores Garcia. The headline reads, "Miss C.S.O 1960."